THE POLICY IMPLEMENTATION OF UTILIZATION OPERATIONAL AID TO SCHOOL PROGRAM FUND (BOS) IN INDONESIA - Supriyadi, Dikdik (EARR (Educational Administration Research and Review), 2017)
The research on the implementation of Operational Aid to School Program (In Indonesian language is abbreviated as BOS) usage policy in Indonesia is aimed to know the description related to the central government program to provide funding for non personnel operating expenses for primary and secondary education units. The method used in this research is qualitative, data collection technique using Focus Group Discussion, interview, observation and documentation. Informants are drawn from the element of the school, the elements of the school committee, the element of the School Board, the element of the Education Office. Submission of Operational Aid to School Program has been right target, component designation and the mechanism is clear although still found the lack of accuracy in its use, because it is still possible because there are still not really understand it. It is certainly necessary to improve the quality and quantity side of socialization. In addition, controls and consents are still underway to improve their effectiveness. It is also realized that the use of Operational Aid to School Program has an impact on the quality of education. At the moment the negative impacts appear to be as soon as possible to find the right solution and keep in mind the tips/strategies to handle it.